Stabilization of uncoupled PVTOL aircraft based on a Lyapunov function - Turker, Turker; Gorgun, Haulk; Cansever, Galip (SAGE PUBLICATIONS LTD, 2012)
In this paper we present a stabilization procedure for PVTOL (planar vertical take off and landing) aircraft with zero coupling coefficient that is defined as the effect of rolling moment on lateral acceleration. A stabilizing control structure has been designed via Lyapunov's direct method including almost the whole state space and its asymptotic convergence has been proven using La Salle's invariance principle. Simulation results have illustrated the effectiveness of proposed control algorithm.
Keywords: La Salle's invariance principle; Lyapunov-based control design; PVTOL aircraft; GLOBAL STABILIZATION; SYSTEMS; Automation & Control Systems; Instruments & Instrumentation